Trends and Problems in Inclusive Education Research from 2018 to 2023: Bibliometric Analysis - Suhendri Suhendri; Afif Alfiyanto; Chandra Murdiono Lisabe; Wulan Sari; Budi Mardikawati (Edumaspul: Jurnal Pendidikan, 2024)
Using a bibliometric approach, this study analyses trends and problems in inclusive education research from 2018 to 2023. The data was taken from the Scopus database, with 200 publications found, sorted into 159 relevant articles, and then analyzed using the Biblioshiny software. The results showed a significant increase in the number of publications related to inclusive education, with the most significant spikes occurring in 2019 and 2020, with 46 articles each. The most frequently emerged keywords were inclusive education, special needs, disability, and inclusive pedagogy, which reflected the main focus on special needs and inclusive pedagogy. Geographical distribution shows that the research is dominated by developed countries such as the United States, the United Kingdom, and Australia, while developing countries still contribute relatively little. The network of collaboration between researchers is strong among developed countries, but cross-country collaboration with developing countries is still limited. The main problems identified in the literature are lack of teacher training, limited resources, and cultural resistance. In addition, there is a research gap in inclusive education at the university level and a lack of concrete solutions to address existing problems. This research provides important insights into the development of inclusive education research. It identifies areas that still need further exploration, especially in developing countries and in the context of higher education.